Tingkat Respon Superovulasi dan Produksi Embrio In Vivo dengan Sinkronisasi CIDR (Controlled Internal Drug Releasing) Pada Sapi Donor Simmental - Jodiansyah, S.; Imron, M.; Sumantri, C. (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2013)
The improvement and increasing of beef cattle population through the application of superovulation and embryo transfer technology is very useful for the development of breeding and industrial feedlot. The purpose of this research to improve the effectiveness of the CIDR on estrus synchronization, superovulation response and the quantityand quality of in vivo embryos in Simmental cattle. Totally 20 Simmental cows were used as dono rswith aged between2.5 - 4years, 10 cows as control with natural estrustreatment(P1) and10 cows for synchronization with CIDR treatment(P2). Parameters observed super ovulation response rate,the number ofcorpusluteum(CL), number of ova,embryos,and Recovery Rate (RR). All data were analized by Chi-square test.The results showed that the treatment of superovulation CIDR based on synchronization had no a significant effecton number of corpusluteum(CL), ovum,and, number of transferableembryoes.